2000
DOI: 10.1128/mcb.20.19.7183-7191.2000
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Functional Interaction between the Eukaryotic Orthologs of Prokaryotic Translation Initiation Factors IF1 and IF2

Abstract: To initiate protein synthesis, a ribosome with bound initiator methionyl-tRNA must be assembled at the start codon of an mRNA. This process requires the coordinated activities of three translation initiation factors (IF) in prokaryotes and at least 12 translation initiation factors in eukaryotes (eIF). The factors eIF1A and eIF5B from eukaryotes show extensive amino acid sequence similarity to the factors IF1 and IF2 from prokaryotes. By a combination of two-hybrid, coimmunoprecipitation, and in vitro binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
104
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 82 publications
(108 citation statements)
references
References 48 publications
4
104
0
Order By: Relevance
“…The accumulation of eIF1A on 48S complexes in the fun12-td strain (Fig. 1C) combined with the results of prior studies revealing a direct interaction between the C termini of eIF5B and eIF1A (9,24,28) led us to test the functional importance of the eIF5B-eIF1A interaction. Replacing the last five residues of eIF1A (residues 149 to 153, encoding DIDDI) with alanine (the mutant named eIF1A-5A) resulted in a slow-growth (Slg Ϫ ) phenotype on synthetic complete (SC) medium containing all amino acids ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The accumulation of eIF1A on 48S complexes in the fun12-td strain (Fig. 1C) combined with the results of prior studies revealing a direct interaction between the C termini of eIF5B and eIF1A (9,24,28) led us to test the functional importance of the eIF5B-eIF1A interaction. Replacing the last five residues of eIF1A (residues 149 to 153, encoding DIDDI) with alanine (the mutant named eIF1A-5A) resulted in a slow-growth (Slg Ϫ ) phenotype on synthetic complete (SC) medium containing all amino acids ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…eIF1A functionally coordinates with eIF1 and promotes 43S complex formation, as well as ribosomal scanning and AUG start codon recognition (12,23,29). In addition to these early roles in the translation pathway, eIF1A physically and functionally interacts with eIF5B (9,24,28). The C terminus of eIF1A binds to eIF5B, and structural analysis revealed that the eIF1A C-terminal residues pack into a groove formed by helices H13 and H14 in C-terminal domain IV of eIF5B (24).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(64) Domain IV is essential for eIF5B function and interacts with eIF1A, suggesting that the release of eIF1A and eIF5B from the ribosome could be coupled. (57) Thus, formation of an elongationcompetent 80S ribosome requires two distinct GTP hydrolysis steps, which predominantly serve as checkpoints for proper AUG codon identification and 80S assembly.…”
Section: Assembly Of the 80s Ribosomementioning
confidence: 99%
“…eIF1A has also been implicated in other aspects of translation initiation. It was shown to promote binding of the ternary complex to the 40S subunit, (56) it binds to eIF5B (the homologue of bacterial IF 2), (57) primarily through their CTDs, and the NTD of eIF1A binds to eIF2 and eIF3. (58) The NMR solution structure of eIF1A shows a modular organisation with an unstructured, basic NTD, a central five-stranded b-barrel oligonucleotidebinding (OB) domain, responsible for sequence-independent binding to single-stranded RNA, and an additional acidic CTD comprising two a-helices followed by an unstructured tail.…”
Section: Introductionmentioning
confidence: 99%